Subtalar Distraction Arthrodesis. (August 2021) - Probe, Robert; Brown, Jaycen C.
Abstract : Summary: Subtalar distraction arthrodesis is a hindfoot reconstructive procedure designed to treat posttraumatic sequelae of certain calcaneal fractures. This video demonstrates one method of performing this procedure which resulted in dramatic pain improvement and functional restoration.